O gesto musical do baterista na música de concerto : um estudo da obra Chronos X de Roberto Victorio - Schwarz, Ricardo Kalan (2017)
The present work has as general objective to verify that forms the musical gesture contributes for the expressive execution of the work the Brazilian composer‟s Roberto Victorio Chronos X, with focus in the gestualidade produced by the interpreter in the execution of the drums of this work, composite for drums and traverse flute. It was had, as starting point, the process of maturation of the interpreter‟s gesture that at the beginning is usually rudimentary and without expressiveness, but that in the course of time according to the rehearsals, studies and accomplished plannings, it goes if developing until the execution more improved. Same immanent of doing musical, the musical gesture there is only some time became object of research of stamp musicological, compositional or interpretative. In if treating of gesture, it is not only a simple mechanical movement that a individual can do, but, I move endowed with meaning and intention that it looks for to express ideas, thoughts, psychic states, feelings, etc. The methodology developed in this work was based, firstly, in the search for a larger understanding of the word gesture and their several use forms in the daily life. Later, the pretension was to discuss about its manifestation, in the musical context and specifically in the extent of the percussion instruments, with special attention to the drums. In a second moment, the discussion was accomplished regarding the transformations by the which the music passed in the century XX, where new creation forms and composition innovators that were denominated by Music of Vanguard appeared. Soon afterwards, the presentation of some aspects related to the thought is had musical-compositional of Roberto Victorio and his slope denominated own Ritual Music, term originating from of the etnomusicologia. It is last the description on the characteristics of his work Chronos X that has as theme the multiplicity of the time expressed through the writing of the score. In the last time of this work the description of the whole course of the process of construction of the performance of Chronos X is had accomplished by the interpreter, that begins starting from the first Reading of the score, going by the process of memorization of the work through the individual rehearsals, until the elaboration procedure and obtaining of gestures capable of grant it a character expressive performative. For each stage of this performative construction they were recorded video that served as tools of analysis of the obtained results, once of the first reading for the end of the study significant changes were verified in relation to the gestures, that initially were rudimentary and in the course of time they became expressive.